Genetic and Non-Genetic Factors Affecting Reproductive Traits of Pakhribas Pig in Nepal - Neopane, Shreeram P. (Nepal Agriculture Research Journal, 2014)
Pakhribas pig is a black colour pig and is highly preferred by the people in the Eastern hills of Nepal. This breed was developed in Nepal by three-way crossing of exotic breeds (Saddle back, Fayuen and Tamworth) at Agricultural Research Station (ARS), Pakhribas, the then Pakhribas Agricultural Centre (PAC). The data of 348 pigs, born over a period of fifteen years (1990 to 2004) were used to study the effect of non-genetic factors on reproductive traits and estimate their genetic parameters. The findings revealed that the overall gestation length and farrowing intervals were 113.7 ± 0.12 days and 182.5 ± 2.2 days, respectively. Season of birth and parity of dams were not important sources of variation for reproductive traits, where as year affected these traits significantly. Heritability estimates of gestation length was low (0.02 ± 0.094), but heritability for farrowing interval was moderate (0.14 ± 0.147) suggesting selection based on farrowing interval would bring the improvement in the trait. Nepal Agric. Res. J. Vol. 8, 2007, pp. 77-81 DOI: http://dx.doi.org/10.3126/narj.v8i0.11584